Performance analysis of intrusion detection systems using the PyCaret machine learning library on the UNSW-NB15 dataset - Abdullah; Iqbal, Faisal Bin; Biswas, Srijon; Urba, Rubabatul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.